Peningkatan Berpikir Kritis pada Mata Pelajaran Sejarah Melalui Pendekatan Pembelajaran Konstruktivistik - Rudi Hermanto (Jurnal Pendidikan Sejarah, 2016)
This study aims to determine the effect of constructivist learning approach on improving critical thinking skills and learning outcomes of learners history . The method used in this study is action research method to the design of the spiral model Kemmis and Taggart . The instruments used are the guidelines for the observation of critical thinking skills and learn the history of the test results . Subjects were students of class XII IPS 3 SMA Negeri 42 Jakarta totaling 33 people . The results are: (1) Application of constructivist learning approach can improve critical thinking skills and learning outcomes of the History of learners ; (2) Planting material concepts through constructivist learning model can accelerate and facilitate the understanding of the learners; (3) Through the constructivist learning approach learners are becoming increasingly active in finding and exploring new knowledge; (4) In the process constructivist learning approach to attract learners in studying the history lesson .